Association of Bone Mineral Density Status with Ethnicity and Parity in females of Karachi - Madeeha Sadiq, Mubina Lakhani, Santosh Kumar Sidhwani, Rosheena Nabeel Khan, Nabila Rasheed, Nuzhat Hassan (Pakistan Journal of Medical & Health Sciences, 2022)
Aims: To assess the association of BMD (bone mineral density) with ethnicity and parity in females of Karachi, Pakistan. Study design: Cross Sectional. Place and duration of study: Department of Anatomy & Nuclear Medicine, Ziauddin Hospital, Clifton Campus, Karachi, Pakistan between March and August 2016. Methods: 200 females aged 40 years and above were included. Average age was 60.7 years (±10.52). BMD assessment was done on DXA scans. Participants were interviewed to obtain baseline demographic characteristics. Statistical Package for Social Sciences (SPSS) version 20 was used to analyze data. Results: No significant association was found between BMD and the different ethnicities or parity in our study population. Conclusion: Bone mineral density is not affected by the number of pregnancies or ethnicity.